2017
DOI: 10.1038/mi.2016.42
|View full text |Cite
|
Sign up to set email alerts
|

Gut commensal Bacteroides acidifaciens prevents obesity and improves insulin sensitivity in mice

Abstract: In humans, the composition of gut commensal bacteria is closely correlated with obesity. The bacteria modulate metabolites and influence host immunity. In this study, we attempted to determine whether there is a direct correlation between specific commensal bacteria and host metabolism. As mice aged, we found significantly reduced body weight and fat mass in Atg7 mice when compared with Atg7 mice. When mice shared commensal bacteria by co-housing or feces transfer experiments, body weight and fat mass were sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
225
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(242 citation statements)
references
References 51 publications
(58 reference statements)
15
225
1
1
Order By: Relevance
“…The gut microbiota also regulates the G-protein-coupled bile acid receptor 1 (known as TGR5) (44). Our group has detected increased levels of bile acids in fecal tissue as well as TGR5 in adipose tissue from B. acidifaciens -fed mice (45). Additional studies have suggested that bile acid-TGR5-cAMP signaling pathways enhance energy expenditure in adipose tissue (46, 47).…”
Section: Microbial Regulation Of Metabolitesmentioning
confidence: 87%
“…The gut microbiota also regulates the G-protein-coupled bile acid receptor 1 (known as TGR5) (44). Our group has detected increased levels of bile acids in fecal tissue as well as TGR5 in adipose tissue from B. acidifaciens -fed mice (45). Additional studies have suggested that bile acid-TGR5-cAMP signaling pathways enhance energy expenditure in adipose tissue (46, 47).…”
Section: Microbial Regulation Of Metabolitesmentioning
confidence: 87%
“…This shift has significant effects on GH and sugar metabolism in these taxonomic groups. Species such as B. acidifaciens and B. uniformis ameliorate obesity by immunomodulation and improved host metabolism (Gauffin Cano et al, 2012; Yang et al, 2017). However, the mechanism for these effects is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, the abundances of Bacteroides (most abundant sequence: Bacteroides acidifaciens) and Ruminococcus (most abundant sequence: Clostridium fusiformis) correlated negatively with the weight of epididymal adipose tissue. Most recently, Yang et al (32) reported that Bacteroides acidifaciens was significantly increased in feces of dendritic cell-specific autophagyrelated gene 7 (Atg7)-deleted mice, and that the body weight and fat mass of the mice were reduced when compared with control mice. Furthermore, mice fed with Bacteroides acidifaciens showed elevated concentrations of insulin and glucagon-like peptide-1 in the serum, thereby reducing the body weight and fat mass.…”
Section: Discussionmentioning
confidence: 99%